2022
DOI: 10.1038/s41380-022-01764-8
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic aetiologies for childhood speech disorder: novel pathways co-expressed during brain development

Abstract: Childhood apraxia of speech (CAS), the prototypic severe childhood speech disorder, is characterized by motor programming and planning deficits. Genetic factors make substantive contributions to CAS aetiology, with a monogenic pathogenic variant identified in a third of cases, implicating around 20 single genes to date. Here we aimed to identify molecular causation in 70 unrelated probands ascertained with CAS. We performed trio genome sequencing. Our bioinformatic analysis examined single nucleotide, indel, c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…The expanding list of genes associated with CAS highlights the importance of performing genetic testing for monogenic disorders. 4 Our report expands the documented phenotypes associated with ZNF292-related NDD by characterizing more fully the feeding and speech difficulties as OMA, VPI, and CAS. This report also expands the list of genes to consider in the differential diagnosis of ID, ASD, and CAS.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The expanding list of genes associated with CAS highlights the importance of performing genetic testing for monogenic disorders. 4 Our report expands the documented phenotypes associated with ZNF292-related NDD by characterizing more fully the feeding and speech difficulties as OMA, VPI, and CAS. This report also expands the list of genes to consider in the differential diagnosis of ID, ASD, and CAS.…”
Section: Discussionsupporting
confidence: 59%
“…A novel de novo pathogenic variant [c.3432_3436del; p.(N1114Kfs*5)] was discovered in our patient, which has not been previously described. The expanding list of genes associated with CAS highlights the importance of performing genetic testing for monogenic disorders 4 …”
Section: Discussionmentioning
confidence: 99%
“…Second, speech and language disorders have considerable overlap with neurodevelopmental disorders, movement disorders, and epilepsy. 13,32 Lastly, distinct speech phenotypes can be associated with specific genotypic findings and demonstrate genetic overlap with known neurodevelopmental genetic conditions. 2,4,6 As expected, our analysis of speech diagnoses showed that, even though there were a total of twenty-six ICD-10 codes corresponding to this broad clinical presentation, the broader phenotypic diagnoses were the most frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Second, speech and language disorders have considerable overlap with neurodevelopmental disorders, movement disorders, and epilepsy. 13,32 Lastly, distinct speech phenotypes can be associated with specific genotypic findings and demonstrate genetic overlap with known neurodevelopmental genetic conditions. 2,4,6…”
Section: Discussionmentioning
confidence: 99%
“…Following this, additional inherited and de novo disruptive FOXP2 variants have been implicated in speech/language deficits (with CAS as the most prominent phenotype) in multiple independent families and probands [11], but these still explain only a small proportion of cases overall [12]. In recent years, systematic exome/genome sequencing screens of CAS cohorts have begun to identify potential high-penetrance pathogenic variants in genes beyond FOXP2 [6,[13][14][15]. Most of the genetic loci highlighted by such CAS screens have also been implicated in heterogeneous neurodevelopmental disorders, in which speech problems may occur in the context of a more pervasive syndrome, with notable examples including CHD3 [16] (MIM: 618205), SETD1A [17] (MIM: 619056), WDR5 [18], and SETBP1 [19] (MIM: 616078).…”
Section: Introductionmentioning
confidence: 99%